THE USE OF ENGLISH SHORT STORIES TO ENRICH STUDENTS’ VOCABULARY MASTERY - Putri, Andi Sri Mega; Munir, Munir; Farahdiba, Syarifah (Universitas Negeri Makassar, 2023)
The objective of the research was to find out whether the use of short stories can enrich students’ vocabulary mastery: meaning, spelling, pronunciation, word form and word use. The researcher applied a pre-experimental method. The population was the eighth-grade students of SMP Negeri 29 Makassar in academic year 2022-2023 and the sample of this research were 29 students from class VIII/7 by using cluster random sampling. The data were collected through test (pre-test and post-test). The result of data analysis stated that the mean score of pre-tests (68.79 with standard deviation 51.34) was lower than mean score of post-tests (82.82 with standard deviation 13.32) therefore the value of t-test (1.14 with significant difference 0.000) level of significance (α) = 0.05 and degree of freedom (df) = 28. It shows that the alternative hypothesis of this research is accepted. based on the finding and discussion of the study, the researcher concludes that using short stories can enrich students’ vocabulary mastery at the eighth grade of SMP Negeri 29 Makassar.